Using the human capabilities approach as a normative framework to evaluate institutional teaching and learning interventions at UWC - Bozalek, Vivienne; Dison, Arona (South African Journal of Higher Education, 2016)
Involving mainstream academics across the institution in re-examining their pedagogical practices at higher education institutions has recently been put forward as an effective strategy for institutionalising transformation in teaching and learning (D’ Andrea and Gosling 2005; Vogel 2010; Winberg 2011). This can be contrasted to an academic ‘development’ approach where those who are regarded as experts (academic developers) bring enlightenment to mainstream academics who are regarded as ‘less than’ and in need of development (D’ Andrea and Gosling 2005; Manathunga 2006; Vogel 2010). This process, while having the interests of students at heart, could be seen as decontextual and more importantly, as dehumanising and disparaging towards academics (Vogel 2010). This paper makes use of the human capabilities normative framework to evaluate the implementation of a process of institutionalising teaching and learning interventions at the University of the Western Cape (UWC). More particularly, it focuses on one strategy which was adopted to achieve a change in the practice and culture of teaching and learning across the institution – teaching and learning retreats for Heads of Academic Departments (HoDs).